’MANKAN’ FISHERY OF THE DWARKA COAST - Bhaskaran, M; Gopalakrishnan, P; Chandy, Mohan (Indian Journal of Fisheries, 2011)
Characteristics of a seasonal fishery of the grey mullet, Valamufil seheli (Forsk.), locally known as ’Mankan’, conducted along the Dwarka coast are described.